SCREENING OF RADICAL SCAVENGING EFFICACY OF MELANIN ISOLATED FROM ASPERGILLUS FUMIGATUS - NITYA MEENAKSHI R; SUGANTHI R (International Journal of Pharma and Bio Sciences, 2013)
Production of melanin is one of the most universal, but at the same time enigmatic adaptations of living organisms to the variable conditions on the earth. The presence of various kinds of melanin in representatives of almost every large taxon suggests an evolutionary importance of melanogenesis. Melanin could be a cause to induce virulence as well as enhancing the survival capability of the fungus under stress, leading to its success as a cosmopolitan species. This study was designed to appraise the antioxidant potential of melanin from Aspergillus fumigatus. Melanin was isolated from its conidial forms by alkaline extraction and acid hydrolysis. An initial antioxidant assay with respect to DPPH and ABTS radicals was carried out following which a detailed antioxidant screening assays were performed that includes valuation of peroxides, hydroxyl radicals, oxides, superoxides etc.,. This report delineating the antioxidant potential shows that the melanin extracted gives scientific basis for its use as potent antioxidant and favours antioxidants from biological samples to have a better advantage of applications. The slight increase in the activity shown thus favours antioxidants from biological samples to have a better advantage of applications when compared to samples synthetically or chemically obtained. This in turn reveals that the lipid soluble defence antioxidant also may have a role to play in the survival of the fungus in immune-compromised hosts.